PWE-006 The T-piece pull technique removal of PEG buried bumpers – a quick novel endoscopic technique. (June 2019) - Hollingworth, Thomas; Boger, Philip; Clarke, E; Patel, P; Rutter, C; Smith, T; Rahman, Imdadur
Abstract : Introduction: Buried bumper syndrome (BBS) represents a rare, but potentially serious complication in percutaneous endoscopic gastrostomy (PEG) tubes. In BBS there is a growth of the gastric mucosa over the inner bumper of the PEG tube, affecting 0.–% of PEG tubes. Options for the management of BBS include the insertion of a jejunal extension, surgical or endoscopic removal. Endoscopic removal represents the most attractive option as it is the least invasive procedure to remove the buried bumper (BB). Several endoscopic techniques have been described including endoscopic dissection (ESD) of the overgrown tissue, a "Push-pull T technique", or the use of a papillotome placed through the PEG tube to cut the overgrown tissue. The novel T-piece pull technique has been developed as a modification of the "Push-pull T technique" without the need for external support. Methods: A prospectively kept database was analysed for all BBS patients undergoing the procedure between September 2016 to January 2019. Primary outcome measures were technical success, procedural times and adverse events. Secondary outcome measures were BB morphology based on Paris polyp classification and PEG dwell time. Description of technique (Figure 1): Following endoscopic assessment of the BB, the PEG tube is exposed and cleaned. The PEG tube is cut close to the abdominal wall. Biopsy forceps are passed through the PEG tube into the stomach under direct endoscopic vision. The forceps pull a 10mm snare passed down the biopsy channel of endoscope out of the stomach through the PEG tube. A 2cm piece of the redundant PEG tube is cut and placed through the snare and closed to create a t–piece. The snare is pulled firmly through the PEG into the stomach, removing the buried bumper. Results: A total of 27 cases for BBS were undertaken with the T-Piece pull technique, on 18 females and 9 males with a mean age of 43 (range 1–8). The median PEG tubes dwell time was 14 months. Procedures were performed with conscious sedation in 19% and enhanced sedation with anaesthetic support in 81%. BB morphology was Paris 1s in 9, 2a in 16 and 2b in 2. The median procedure time was 18 minutes (range 1–5). The technical success was 93%. 2 failed procedures required surgical removal, both 2b lesions. Complications occurred in 2 cases, 1 episode of sepsis and 1 abdominal pain. Discussion: This novel T-piece pull technique for the removal of BB is a simple endoscopic procedure, using equipment that is readily available in most endoscopy departments. The procedure time is much shorter than more complex endoscopic techniques, such as ESD. Lesions which have a 2b Paris classification indicate a deeply buried bumper and should be considered for a different approach to removal.